2016
DOI: 10.1002/2015jc011526
|View full text |Cite
|
Sign up to set email alerts
|

Storm‐driven bottom sediment transport on a high‐energy narrow shelf (NW Iberia) and development of mud depocenters

Abstract: Bottom sediment transport on the NW Iberian shelf was monitored during a downwelling storm in September 2014. Collected data were analyzed and fed into a 3-D coastal ocean model to understand storm-driven sediment transport on the shelf and its impact on midshelf mud depocenters (MDCs). A significantly enhanced level of bottom sediment resuspension, nearly two orders of magnitude higher than that in the prestorm period, was recorded at the mooring site. Field data analysis reveals that it was induced by a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…During the highly variable downwelling season, the combined effect of waves and currents achieved maximum levels of shear stress, more than sufficient to promote resuspension and erosion of surface sediments that agree with near‐bottom transport events reported by Zhang et al () for this area. This is clearly shown during the autumn and winter cruises (Figures and ) when turbidity values at the inner continental shelf achieved maximum levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During the highly variable downwelling season, the combined effect of waves and currents achieved maximum levels of shear stress, more than sufficient to promote resuspension and erosion of surface sediments that agree with near‐bottom transport events reported by Zhang et al () for this area. This is clearly shown during the autumn and winter cruises (Figures and ) when turbidity values at the inner continental shelf achieved maximum levels.…”
Section: Discussionsupporting
confidence: 88%
“…More recently, modeled wave storm conditions support the important role of waves on the bottom dynamics (Oberle, Storlazzi, et al, ) whose interaction with bottom currents was suggested by Zhang et al () to be the key factor to understand the storm‐driven sediment transport. The presence of a thermohaline front and the possible winnowing effects of internal waves on unconsolidated sediments were also suggested to be important factors that can explain the mud depocenters shoreward and seaward limits, respectively (Zhang et al, , ).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Waves dominate sediment transport in areas of the New Zealand and Australian shelves (Carther & Heath, ; Hale et al, ; Moriarty et al, ; Porter‐Smith et al, ). Wave‐current interactions are significant drivers of sediment resuspension on the Northwest Iberian shelf (Zhang et al, ). The Northwest European shelf experiences high tidal and high wave energy, which is enhanced by wave‐current interactions in areas of strong tidal currents (Hashemi & Neill, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of shelf-scale sediment transport are considering wave-tide coupling more regularly (Dietrich et al, 2011;Moriarty et al, 2014;Xu et al, 2016;Zhang et al, 2016); however, coupled modeling systems are more computationally expensive. A number of studies consider uncoupled tides and waves as an approximation, ignoring wave-tide interactions (e.g., Bricheno et al, 2015;Neill et al, 2010;Porter-Smith et al, 2004;van der Molen, 2002;Xing et al, 2012).…”
Section: 1029/2018jc014861mentioning
confidence: 99%